(untitled) (World Economics and Finance Bulletin, 2023)
In recent years, the digital banking model has been transforming in Uzbekistan, and it is becoming more and more popular and widespread. Banks are investing in the development of this business model. Digital technologies are technologies that use electronic computing equipment to record code pulses in a specific sequence and at a certain frequency. According to Cisco’s surveys, many customers are not satisfied with banking services in general. Digital transformation will be the lifeline for the financial sector. In Uzbekistan, taking into account world experience, President Shavkat Mirziyoyev instructed to implement digitalization projects in various sectors of the economy by 2025. He said: "Without the digital economy, there is no future for the country’s economy."